Fatal spontaneous pneumomediastinum complicating SARS-COV2 pneumonia in a pregnant women - Youssef Motiaa; Siham Alaoui Rachidi; Smael Labib; Hicham Sbai (Wolters Kluwer Medknow Publications, 2023)
Pneumomediastinum was reported as a complication of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pneumonia in the general population. Data concerning the association of this complication with pregnancy are rare. We report a case of a parturient who presented with SARS-CoV-2 pneumonia complicated with pneumomediastinum. The management of Acute respiratory distress syndrome (ARDS) and obstetric approach are also discussed.